The Patterns of Ablaut Reduplication in Toba Batak: A Construction-Based Approach - Ambarita, Esron; Sembiring, Milisi (REiLA : Journal of Research and Innovation in Language, 2025)
The study addresses a critical gap in morphological research by investigating the understudied patterns of ablaut reduplication in Toba Batak (TB), an endangered Austronesian language, through a construction-based approach. While ablaut reduplication has been widely examined in Indo-European languages like English and German, its manifestations in TB remain largely unexplored, despite the language’s cultural significance and vulnerability. This study fills this gap by employing a modified version of Halle’s (1973) generative morphology model, tailored to TB’s unique linguistic features, to analyze data collected from 12 native speakers in Samosir Regency. The findings reveal three distinct categories of ablaut reduplication in TB: verbal (VAR), nominal (NAR), and adjectival (AAR), each exhibiting specific vowel patterns. For instance, monosyllabic words typically alternate between [u]/[e] and [a]/[u], while disyllabic words follow a [u-a] to [a-I]/[a-u] sequence. Notably, the study demonstrates that TB’s ablaut reduplication is unproductive, lacking grammatical meaning and affixation, with lexical meaning derived solely from vowel alternations. The modified Hallean model, incorporating orthographic and phonological rules, proves effective in capturing these nuances, offering a novel framework for analyzing non-Indo-European languages. By documenting these patterns, the study not only enriches the understanding of TB’s morphological system but also contributes to broader linguistic typology and the preservation of endangered languages. The implications extend to applied fields such as language education and cultural revitalization, underscoring the urgency of safeguarding regional languages like TB amidst globalization. This research thus bridges theoretical linguistics and practical conservation efforts, advocating for further studies on underrepresented languages.